CAPM : Certified Associate in project management practice exams - Haner, James L.; McCoy, Cate (McGraw-Hill Education, 2019)
Don't Let the Real Test Be Your First Test! Take the 2018 version of the challenging CAPM exam with confidence using this highly effective, exam-focused study resource. CAPM® Certified Associate in Project Management Practice Exams contains more than 1000 practice questions and is fully aligned with the Project Management Body of Knowledge® Guide, Sixth Edition . All questions simulate those on the live test in content, style, tone, and difficulty. To facilitate retention, every question is accompanied by in-depth explanations for both correct and incorrect answers. Covers all 57 learning objectives for the CAPM exam, including: " roject integration management " roject scope management " roject schedule management " roject cost management " roject quality management " roject resource management " roject communications management " roject risk management " roject procurement management " roject stakeholder management Digital content includes: " est engine that provides full-length practice exams or customized quizzes by chapter or by exam domain " 00 practice exam questions